Development of New Reactions Driven by N–O Bond Cleavage: from O-Acyl Hydroxylamines to Tetrodotoxin - Robins, Jacob G.; Johnson, Jeffrey S. (Synlett, 2023)
This Account describes new reactions that have been developed in the Johnson laboratories at UNC Chapel Hill enabled by considerations of N–O bond cleavage. Three main case studies are highlighted: the metal-catalyzed electrophilic amination of O-acyl hydroxyl amines, multihetero-Cope rearrangements driven by O–N bond breakage, and merged dearomatization/N=O cycloadditions for the synthesis of complex 4-aminocyclohexanols such as those found in the natural product tetrodotoxin.1 Introduction2 Electrophilic Amination3 Multihetero-Cope Rearrangements4 Progress toward a Total Synthesis of (–)-Tetrodotoxin5 Conclusion
Keywords: amination; catalysis; sigmatropic reactions; total synthesis; tetrodotoxin; cycloadditions